Amino-functionalized graphene oxide membranes for efficient separation of Sr2+ ions. (February 2023) - Vishwakarma, Rini K.; Narayanam, Pavan K.; Umamaheswari, R.; Polaki, S.R.
Abstract: Graphene oxide (GO) membranes were integrated with diverse nitrogen functional groups by subjecting to ammonia (NH3 ) vapours and evaluated for resultant changes in their chemical functioning and strontium (Sr) adsorption performance. Exposure to NH3 vapours amends the functional groups of GO, introduces amine, amide, ammonium functionalities and generates abundant sites prone to react with Sr 2+ ions. The extent of GO restructuring and repercussions on Sr adsorption behaviour were examined using different GO precursors, NH3 treatment methods, membranes with varying GO mass and other nitrogen reagents namely, tri-isooctyl amine, pyridine, N, N -dimethyl acetamide. Nitrogen group functionalization enhances the Sr adsorption capacity of GO membranes nearly by two times, irrespective of the NH3 exposure duration and nature of precursor GO membranes. These NH3 subjected GO membranes displayed optimum Sr adsorption performance of ~475 mg/g, reusable at least for nine filtration cycles and importantly, capable of discharging 35–60 % of adsorbed Sr. The N-group supported Sr separation demonstrated in the present work is an energy efficient solid state membrane based procedure, which also lays a road map for development of amine, amide, ammonium functionalized GO layers and provides flexible platform for separation of all those toxic elements displaying affinity to complex with N-groups. Graphical abstract: Unlabelled Image Highlights: Demonstrates controlled N-group functionalization of GO membranes for Sr adsorption. Optimum Sr adsorption capacity of ~475 mg/g and recovery of 35–60 % of adsorbed Sr. Comprehensive analysis of N-functionalization of GO sheets with diverse N-reagents. Promote unmediated solid state interactions among pristine NH3 vapours and GO sheet. Launches energy efficient method for amine, amide, ammonium functionalization of GO.